Migrant Women-experiences from the Mediterranean Region - La Cascia, Caterina (Clin Pract Epidemiol Ment Health, 2020)
INTRODUCTION: The phenomenon of migration is characterized and influenced by a number of different variables; and the different stages of journey are related to different levels and types of psychological distress. Women, in particular, are exposed to further specific risks during migration. AIM: To determine the factors that affect the psychological health of migrant women during the different stages of the migration journey. METHODS: We provide a narrative review of the literature around the experiences of women during migration process, with a geographical focus on women migrating to the Mediterranean area. RESULTS: Little data is currently available on the burden of mental health disorders for female migrants. Most studies about the mental health status of migrants were not gender-disaggregated or focused specifically on migrant women’s experiences of violence. Sexual and Gender-Based Violence (SGBV) was found to be a common risk factor faced by all the women who leave their native country to migrate to other countries. CONCLUSION: Despite the importance of the issue and the gender-specific variables related to the experience of migrant women, few studies have looked specifically at psychological variables and mental health status in the female migrant population. It is crucial that future studies are conducted around female migration, violence towards women, and women’s mental health, in order to provide an evidence-base for promoting adequate policies and prevention/treatment programs for women.